Black hole evaporation beyond the Standard Model of particle physics - Michael J. Baker; Andrea Thamm (Journal of High Energy Physics, 2023)
Abstract The observation of an evaporating black hole would provide definitive information on the elementary particles present in nature. In particular, it could discover or exclude particles beyond those present in the standard model of particle physics. We consider a wide range of motivated scenarios beyond the standard model and identify those which would be best probed in the event of an observation. For those models we define representative benchmark parameters and characterise the photon spectra as a function of time. For the supersymmetric benchmark model, where most of the new particles produce secondary photons, we provide secondary spectra and discuss the subtle interplay between faster black hole evaporation and an increased flux of secondary photons. Finally, we discuss the impact of these models on future experimental analysis strategies.